Capacity Building for Women Farmers in Organic Waste Management and SRI-Based Cultivation - Jasminarni, Jasminarni; Novita, Trias; Andayani, Jul (Jurnal Karya Abdi Masyarakat, 2025)
This study aims to enhance sustainable agriculture by implementing the System of Rice Intensification (SRI) through the utilization of rice straw compost among the Sedap Malam Women Farming Group in Koto Pudung, Kerinci. The method involves a participatory training approach focused on transforming rice straw waste into high-quality organic fertilizer, addressing the ecological drawbacks of conventional biomass burning. Results indicate that integrating rice straw compost into SRI framework significantly optimizes nutrient recycling and soil health restoration while reducing production costs by eliminating dependence on synthetic fertilizers. The novelty of this work lies in the localized synergy between organic waste management and SRI principles to empower women farmers in a rural context. Ultimately, this transition from traditional burning to organic composting serves as a strategic implication for mitigating air pollution and fostering a circular economy in regional rice production.